Oxidative rearrangement of stilbenes to 2,2-diaryl-2-hydroxyacetaldehydes - Kalshetti, Rupali G.; Ramana, V. Chepuri (ACS Omega, 2020)
A one-pot oxone-mediated/iodine-catalyzed oxidative rearrangement of stilbenes leading to 2,2-diary1-2-hydroxyacetaldehydes is described. Control experiments revealed that a 2,2-diarylacetaldehyde was initially formed that undergoes subsequent alpha-hydroxylation. The resulting alpha-hydroxyaldehydes have been subjected to a one-pot Still Gennari olefination followed by cyclization, leading to S,S-diaryl-y-butenolides.